Maintaining Intergenerational Solidarity in Mexican Transnational Families - Catherine A. Solheim; Jaime Ballard; Patricia D. Olson (Journal of Human Sciences and Extension, 2016)
This study explored how Mexican transnational families maintain intergenerational relationships, using five of the dimensions of the intergenerational solidarity framework. Interview data from 13 adult migrant children who lived in the U.S. and their parents who lived in Mexico were analyzed. Structural solidarity was challenged by great distance between families. Families maintained associational solidarity by making contact frequently, though visiting was often restricted by lack of documentation. Functional solidarity was expressed through financial support to parents. This involved remittances sent to parents. However, it should be noted that it was often migrants’ siblings in Mexico who managed these remittances. Affectual solidarity was expressed through statements of love and concern for one another. Normative solidarity and consensual solidarity reflected the value of familismo through financial support and the desire to live together. Several dimensions of intergenerational solidarity are interconnected. This study provides evidence for the relevance of the intergenerational solidarity framework in transnational families and suggests that geographic context is relevant when studying intergenerational relationships.